2012
DOI: 10.1063/1.4745481
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mass dependence of point-to-set correlation length scale in polymers

Abstract: We use a recently proposed metric, termed the point-to-set correlation functions, to probe the molecular weight dependence of the relevant static length scales in glass-forming oligomeric chain liquids of 4, 5, 8, and 10 repeat units. In agreement with the results for simple, monatomic fluids, we find that static length scales of the oligomers increase monotonically when the temperature is lowered towards the glass transition temperature of the fluid. More interestingly, the static length scale increases with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 55 publications
1
3
0
Order By: Relevance
“…Figure b compares Δ T vs h eff with Δ T vs h , where it is seen that the h eff values for polymer confinement effects to become noticeable (30–50 nm) are generally larger and closer to the length scales typically reported in thin film studies. The critical h eff values also fall within the limit of 20 R g of the host polymer suggested by recent computer simulations …”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…Figure b compares Δ T vs h eff with Δ T vs h , where it is seen that the h eff values for polymer confinement effects to become noticeable (30–50 nm) are generally larger and closer to the length scales typically reported in thin film studies. The critical h eff values also fall within the limit of 20 R g of the host polymer suggested by recent computer simulations …”
Section: Resultssupporting
confidence: 75%
“…Molecular simulations by Ganesan et al 42 reported that much smaller surface-to-surface distances between nanoparticles are needed in PNCs to produce quantitatively similar effects on T g as in polymer thin films, which is consistent with our findings. A more concrete understanding of this point is possible by using an analogy to fluid flow in porous particle beds to compute the effective separation between flat plates, h eff = (D eff /3)[(1 − ϕ eff )/ϕ eff ], 43 required to achieve the same flow resistance. Here D eff and ϕ eff are the nanoparticle diameter and volume fraction, including the polymer brush height (Δ), respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both research fields are linked by the long tradition to receive information about length scales of glassy dynamics from confined liquids [5][6][7]. To avoid spurious liquid-matrix interactions, recent simulation studies pinned appropriate fractions of particles of a bulk liquid so as to obtain confining matrices consisting of the same type of particles as the confined liquid [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. While the strong slowdown of dynamics near interfaces is accompanied by a substantial perturbation of the structure for most matrices, the slower dynamics occurs in an unperturbed structure for such neutral matrices [18,26,31].…”
mentioning
confidence: 99%